Characterization and genomic analysis of a novel halovirus infecting Chromohalobacter beijerinckii - Yi, Hao; Fu, Chaoqun; Diao, Kaixin; Li, Zhiying; Cui, Xiaolong; Xiao, Wei (Frontiers in Microbiology, 2022)
Bacteriophages function as a regulator of host communities and metabolism. Many phages have been isolated and sequenced in environments such as the ocean, but very little is known about hypersaline environments. Phages infecting members of the genus Chromohalobacter remain poorly understood, and no Chromohalobacter phage genome has been reported. In this study, a halovirus infecting Chromohalobacter sp. F3, YPCBV-1, was isolated from Yipinglang salt mine. YPCBV-1 could only infect host strain F3 with burst size of 6.3 PFU/cell. It could produce progeny in 5–20 % (w/v) NaCl with an optimal concentration of 10 % (w/v), but the optimal adsorption NaCl concentration was 5–8 % (w/v). YPCBV-1 is sensitive to pure water and depends on NaCl or KCl solutions to survive. YPCBV-1 stability increased with increasing salinity but decreased in NaCl saturated solutions, and it has a broader salinity adaptation than the host. YPCBV-1 has a double-stranded DNA of 36002 bp with a G+C content of 67.09% and contains a total of 55 predicted ORFs and no tRNA genes. Phylogenetic analysis and genomic network analysis suggested that YPCBV-1 is a novel Mu-like phage under the class Caudoviricetes. Auxiliary metabolic gene, SUMF1/EgtB/PvdO family non-heme iron enzyme, with possible roles in antioxidant was found in YPCBV-1. Moreover, DGR-associated genes were predicted in YPCBV-1 genome, which potentially produce hypervariable phage tail fiber. These findings shed light on the halovirus-host interaction in hypersaline environments.